Microstructure and Mechanical Behavior of Hot Extruded Aluminum/Tin-Bismuth Composites Produced by Powder Metallurgy - Adnan Khan; Penchal Reddy Matli; Muddasir Nawaz; Manohar Reddy Mattli; Gururaj Parande; Vyasaraj Manakari; Abdul Shakoor; Amina Sultan Aljaber; Manoj Gupta (Applied Sciences, 2020)
In this study, Al-BiSn composites were synthesized by a combination of microwave sintering and hot extrusion processes. The structural, morphological, mechanical, and thermal properties were investigated to elucidate the role of Bi60Sn40 (BiSn) alloy content (5, 10, and 15 wt.%) in modifying the properties of Al-BiSn composites. The X-ray diffraction (XRD) patterns confirmed the presence of aluminum and BiSn particles. Distribution of BiSn particles in Al-BiSn composites was confirmed by field emission scanning electron microscopy associated with energy dispersive X-ray analysis (FE-SEM-EDX). Results indicated that hot extruded Al-(15 wt.% BiSn) composite exhibits maximum hardness (78 ± 4 Hv) and tensile strength (185 ± 3 MPa), which were 117% and 58% improvements, respectively, compared to pure Al. This improvement in mechanical properties can be attributed to the strengthening effect of BiSn particles. A decline in the values of the coefficient of thermal expansion (CTE) with an increasing amount of BiSn particles reflects the enhanced thermal stability of developed Al-BiSn composites. The promising properties of Al-BiSn composites make them suitable for many industrial applications.